Dinamika Populasi Hama dan Penyakit Utama Tanaman Jagung Manis (Zea mays saccharata Sturt) pada Lahan Basah dengan Sistem Budidaya Konvensional serta Pengaruhnya terhadap Hasil di Denpasar-Bali - RONDO, SALBERD FERDINAN; SUDARMA, I MADE; WIJANA, GEDE (Agrotrop : Journal on Agriculture Science; Vol 6 No 2 (2016), 2016)
Dynamics of Pest Population and Main Diseases of Sweet Corn Plants (Zeamays saccharata Sturt) at Wetland with Conventional Cultivation Systemand Their Effect on Yields in Denpasar-Bali. The study was conducted usingsurvey techniques of pests and diseases in paddy fields belonging to farmers in Denpasar-Bali, which consists of three fields. The three areas were Sidakarya, Renon and Kesiman.Plant samples in each land were taken using the sample plot diagonal method, with the areaof diagonal plot in each land was 3 m x 3 m. Plot observations on each of the specified areaof plant samples was done randomly (lottery) as much as 25% of the total number of plantsper-plot, then observation was done for population growth of pests and diseases, temperature,humidity and crop yield. The observations was started from 1week old plants after planting(MST) to 1 week before harvesting, with intervals of 1 week. Recording the population ofpests and diseases from week to week, the temperature condition and humidity in each areaand the condition of the field ( the existing other plants, mulching). Recorded informationabout conventional cultivation systems applied by each farmer were be explored throughinterview techniques. The data were then analyzed using correlation and regression and weredescriptively explained. The results showed that there were four main types of pests (locusts,seed flies, armyworm and caterpillars cob) and three kinds of major diseases (blight, rust anddowny mildew) associated with sweet corn. The results also showed that there was nosignificant between the correlation dynamics of pest population and diseases withtemperature and humidity. As for the commercial harvest, significant effect was shown by thediseases that had an impact on the decrease in yield in quantity especially downy mildew andpest impact on the quality of yields, especially caterpillar cob.
Keywords: Population dynamics; temperature; humidity; yields